Market concentration in the banking sector: Evidence from Serbia - Miljković, Marko M; Filipović, Sanja; Tanaskovic, Svetozar (Industrija, 2013)
The aim of this paper is to research the level and development of market concentration in the banking sector in Serbia. In the first chapter, the authors presented different concentration theories from economic literature and explained the possible impact of high concentration on various economic parameters. The second chapter provides information on methodology and different indicators used in order to measure the level of market concentration in the banking sector in Serbia. Empirical results of the analysis are presented in the third chapter of the paper and they include concentration of assets, capital, loans, deposits, interest income and net profit (loss) before tax, as well as comparative analysis with Central, Eastern and South European countries. Finally, the last chapter summarizes key messages of the paper.
Keywords: Concentration ratio; Hirschmann-Herfindahl index; Market; Banking; Gini coefficient